Theoretical Prediction for Synthetic Realization: Pyramidal Systems ClE[E′4R4] (E = B–Ga, E′ = C–Ge, R = SiMe3, SiMetBu2): A DFT Study - Olga A. Gapurenko; Vladimir Ya. Lee; Ruslan M. Minyaev; Vladimir I. Minkin (Heteroatom Chemistry)
Structure and bonding of hybrid group 13/14 pyramidal molecules ClE[E′4R4] (E = B–Ga, E′ = C–Ge, R = SiMe3, SiMetBu2) were studied by DFT calculations. Six pyramidal structures are suggested for their potential synthetic realization.